Comparison of Serum Sodium Values in People Consuming Various Types of Salt and their Effect on the Systolic Blood Pressure - Dr Chaganti Sridevi; Dr UVPU Sowjanya; Dr V.S.KalaiSelvi (International Journal of Pharma and Bio Sciences, 2020)
Sodium is one of the electrolytes in the body and a principal cation. When there is an imbalance in sodium consumption and loss, the serum sodium levels are affected causing hyponatremia or hypernatremia. World Health Organisation recommends an intake of salt at the rate of 5 g per day as optimum. Salt is the oldest and most important ingredient in the diet. There are many salt varieties and the study is done comparing serum sodium levels and blood pressure values in a community where subjects are consuming table salt, sea salt, or Himalayan pink salt. The aim of doing the study is to compare the sodium values and systolic blood pressure values in different type of salt users. Blood Samples were obtained from these subjects and analyzed for serum sodium and serum potassium by ISE and blood pressure was measured by a sphygnomanometer. The results showed a significant difference in sodium levels and systolic blood pressure with a particular salt use but it is recommended to use any salt in moderate quantities.